Comparative efficacy and safety of antidepressant therapy for the agitation of dementia: A systematic review and network meta-analysis - Chen, Kaili; Li, Haiqi; Yang, Le; Jiang, Yan; Wang, Qiaoli; Zhang, Jiao; He, Jinting (Frontiers in Aging Neuroscience, 2023)
Considering the lack of direct comparisons between different antidepressants in the treatment of agitated behavior in dementia patients, we conducted the network meta-analysis (NMA) to compare the efficacy and safety of these antidepressants.A systematic literature search was performed for eligible studies published up to November 6th 2022 on four international databases (PubMed, Cochrane Library, Web of Science and Embase) and four Chinese databases (Wanfang Data, China National Knowledge Infrastructure, VIP Database and China biomedical literature service). We included randomized controlled trials (RCTs) reporting the efficacy and safety of antidepressants in treating agitated behavior in dementia patients. The quality of the included studies was judged by two independent reviewers using the Cochrane Handbook for Systematic Reviews of Interventions. A network meta-analysis based on the frequency method was conducted to summarize the comparative efficacy and safety of interventions based on several outcomes. Thirteen studies with 1,169 participants were included in this NMA. Based on the outcome of the agitation score, citalopram (standardized mean difference, SMD = -0.44, 95% confidence interval, 95%CI = -0.72 to -0.16) showed significant benefits over the placebo group. Based on the outcome of the total adverse events, Trazodone (odds ratio, OR=1.52, 95%CI = 0.12 to 2.93) had a higher risk than placebo. Among the antidepressants, citalopram therapy had the highest probability of being the best intervention, based on improvement from baseline to the end of the intervention (SUCRA = 96.9%).